2011
DOI: 10.1055/s-0031-1284433
|View full text |Cite
|
Sign up to set email alerts
|

The Dangers of Gathering Data: Surgeon-Specific Outcomes Revisited

Abstract: The accuracy of risk adjustment is important in developing surgeon profiles. As surgeon profiles are obtained from observational, nonrandomized data, we hypothesized that selection bias exists in how patients are matched with surgeons and that this bias might influence surgeon profiles. We used the Society of Thoracic Surgeons risk model to calculate observed to expected (O/E) mortality ratios for each of six cardiac surgeons at a single institution. Propensity scores evaluated selection bias that might influe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 25 publications
(23 reference statements)
0
7
0
Order By: Relevance
“…Researchers have long attempted to profile provider performance, targeting different types of providers using various measures, with limited success. [1][2][3][4][5][6][7][8] Surgeons have been the focus of numerous profiling efforts focused on postoperative patient outcomes, dating back to the New York Department of Health's publication of mortality rates after coronary artery bypass grafting surgery in the early 1990s. 9 In 2013, the United Kingdom's National Health Service began publishing surgeon-specific patient outcomes.…”
mentioning
confidence: 99%
“…Researchers have long attempted to profile provider performance, targeting different types of providers using various measures, with limited success. [1][2][3][4][5][6][7][8] Surgeons have been the focus of numerous profiling efforts focused on postoperative patient outcomes, dating back to the New York Department of Health's publication of mortality rates after coronary artery bypass grafting surgery in the early 1990s. 9 In 2013, the United Kingdom's National Health Service began publishing surgeon-specific patient outcomes.…”
mentioning
confidence: 99%
“…Looking at six surgeons within one institution, Ferraris et al found that 83% of deaths occurred within the highest quartile for risk. One surgeon had significantly more high-risk patients ( p < 0.05), demonstrating a shunting of high-risk patients and an inordinate risk burden on select physicians for unmeasured reasons [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…At present, hierarchical regression is the gold standard for risk adjustment of outcomes and for producing provider report cards; however this gold standard is rarely used [ 41 ] and no equivalent modeling has been developed in ophthalmology to date. The National Ophthalmic Database (NOD) in the U.K. has compiled a national cataract data set, and participating cataract surgeons have the ability to compare their individual surgical data to others in a risk-adjusted manner [ 28 ].…”
Section: Discussionmentioning
confidence: 99%